2007
DOI: 10.1242/dev.002618
|View full text |Cite
|
Sign up to set email alerts
|

On the carapacial ridge in turtle embryos: its developmental origin,function and the chelonian body plan

Abstract: The chelonian carapace is composed of dorsolaterally expanded ribs; an evolutionary change in the rib-patterning program is assumed to be related to this novelty. Turtle embryos exhibit a longitudinal ridge called the carapacial ridge (CR) on the flank, and its histological resemblance to the apical ectodermal ridge of the limb bud implies its inductive activity in the unique patterning of the ribs. We studied the Chinese soft-shelled turtle, Pelodiscus sinensis, and confirmed by labeling with a lipophilic dye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
124
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(128 citation statements)
references
References 41 publications
4
124
0
Order By: Relevance
“…3B; supplementary materials and methods). This initial condition follows from the observation of a pre-pattern of 12 marginal scute placodes on each carapacial ridge that we hypothesize to be established by the somites, the segmental units of paraxial mesoderm on either side of the neural tube and notochord in vertebrate embryos (Yntema, 1970;Nagashima et al, 2007;Moustakas, 2008). We identified this pre-pattern with the sequentially alternating expression domains of Gremlin-Shh-Bmp in the carapacial ridge that are shown in Fig.…”
Section: A Computational Model Of Scute Formation and Variationmentioning
confidence: 76%
See 1 more Smart Citation
“…3B; supplementary materials and methods). This initial condition follows from the observation of a pre-pattern of 12 marginal scute placodes on each carapacial ridge that we hypothesize to be established by the somites, the segmental units of paraxial mesoderm on either side of the neural tube and notochord in vertebrate embryos (Yntema, 1970;Nagashima et al, 2007;Moustakas, 2008). We identified this pre-pattern with the sequentially alternating expression domains of Gremlin-Shh-Bmp in the carapacial ridge that are shown in Fig.…”
Section: A Computational Model Of Scute Formation and Variationmentioning
confidence: 76%
“…Recent studies of turtle development and paleontology (CebraThomas et al, 2005;Nagashima et al, 2007;Li et al, 2008;Moustakas, 2008;Sánchez-Villagra et al, 2009;Kawashima-Ohya et al, 2011;Kuratani et al, 2011;Hirasawa et al, 2013) have advanced our understanding of the evolutionary origin of turtles and the genetic and cellular interactions that regulate various aspects of bone development in the carapace. However, the genetic regulation of the origin and evolution of the epidermal scutes has not been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…The CR is a bulge of thickened ectoderm overlaying a condensed mesenchyme that first appears in the lateral trunk, dorsal to the lateral somitic frontier running anterior-posteriorly along the flank region, and it has been proposed to be important for directing the shell development (Burke, 1989, Cebra-Thomas et al, 2005, Nagashima et al, 2007. The CR first appears during stage TK14 (according to the staging table of the Chinese soft-shell turtle, Pelodiscus sinensis - Tokita and Kuratani, 2001-; equivalent to stages Yntema 14 of Chelydra serpentina -Yntema, 1968-;and Greenbaum 15 of the hard-shell red-eared slider Trachemys scripta -Greenbaum, 2002-).…”
Section: Introductionmentioning
confidence: 99%
“…Among these genes, Lef-1 is encoding a transcriptions factor that functions as an effector of the canonical Wnt signaling pathway (Behrens et al, 1996). Interestingly, Lef-1 seems to have an important role in controlling the horizontal (not dorsoventral) orientation of the ribs in the carapace (Nagashima et al, 2007). Furthermore, APCDD1 is known to be a target of the canonical Wnt pathway.…”
Section: Introductionmentioning
confidence: 99%
“…He presented a novel and exciting approach that uses sub-micron resolution synchrotron scans to map muscle attachments to fossil bones in 3D that holds great promise for soft-tissue reconstructions in many other contexts. Shigeru Kuratani (RIKEN Center for Developmental Biology, Kobe, Japan) discussed the ribderived turtle carapace as an evolutionary novelty, which results from the arrest and dorsolateral confinement of rib growth, leading to a turtle-specific infolding of the lateral body wall (Nagashima et al, 2007). He showed that the carapacial ridge -a turtle-specific structure that lies along the line of infolding -does not play an inductive role in carapace patterning as previously thought, but instead appears to have co-opted elements of the Wnt signaling pathway for the control of carapace growth.…”
Section: Evolutionary Developmental Biologymentioning
confidence: 99%